2019
DOI: 10.1111/fwb.13246
|View full text |Cite
|
Sign up to set email alerts
|

Functional shifts in lake zooplankton communities with hypereutrophication

Abstract: Functional variation among consumer communities can alter ecosystem nutrient cycling. These impacts on ecosystem function can be specifically driven by interspecific variation in stoichiometric traits; thus, functional trait‐based approaches can be used to explain the processes controlling ecosystem stoichiometry. However, eutrophication may reduce the functional importance of consumers in ecosystems by eliminating heterogeneity in nutrient recycling among taxa. To test whether zooplankton functional diversity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 86 publications
(130 reference statements)
3
37
0
Order By: Relevance
“…Total abundances of meso-zooplankton appeared high, but remained in agreement with other shallow eutrophic lakes [ 32 , 33 , 34 ]. Small zooplanktonic taxa seemed to dominate at the detriment of larger cladoceans, e.g., Daphnia sp., as known from eutrophic temperate lakes of both Europe [ 34 ] and the USA [ 35 ]. As sampling size was low in this study, more research focusing on zooplankton dynamics in that reservoir would be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Total abundances of meso-zooplankton appeared high, but remained in agreement with other shallow eutrophic lakes [ 32 , 33 , 34 ]. Small zooplanktonic taxa seemed to dominate at the detriment of larger cladoceans, e.g., Daphnia sp., as known from eutrophic temperate lakes of both Europe [ 34 ] and the USA [ 35 ]. As sampling size was low in this study, more research focusing on zooplankton dynamics in that reservoir would be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Functional and taxonomic loss and turnover responses have been seen in response to natural and experimental extreme droughts in stream insect communities (Boersma et al 2016, Aspin et al 2018) and functional loss responses were observed in marine intertidal communities along a wave-stress gradient (Valdivia et al 2017). However, a recent study found support for the differential impact hypothesis along a gradient of nutrient pollution in lake zooplankton communities (Moody and Wilkinson 2019). We encourage future work explicitly testing our predictions across different ecosystem types, especially identifying when thresholds of disturbance intensity and different combinations of traits result in markedly different functional and taxonomic responses.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Zooplankton functional traits allow for the identification of the mechanisms that are responsible for various environmental gradients in aquatic ecosystems, including trophic levels, primary productivity (Barnett & Beisner, 2007;Obertegger & Manca, 2011;Oh et al, 2017;Moody & Wilkinson, 2019), temperature (Lokko et al, 2017;Obertegger & Flaim, 2018), depth (Gauthier et al, 2014;Obertegger & Flaim, 2018), hydrological regime (Galir Balkić et al, 2018), salinity (Lokko et al, 2017;Gutierrez et al, 2018) and anthropogenic activity (Simões et al, 2020). The functional traits of zooplankton related to their feeding strategies have been used both to interpret functioning mechanisms in food webs (Kim et al, 2000) and to evaluate the impact of environmental pollution (acidification, turbidity) on ecosystem health and resilience (Hogsten et al, 2009;Petchey et al, 2009;Moreira et al, 2016;Goździejewska et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…The functional traits of zooplankton related to their feeding strategies have been used both to interpret functioning mechanisms in food webs (Kim et al, 2000) and to evaluate the impact of environmental pollution (acidification, turbidity) on ecosystem health and resilience (Hogsten et al, 2009;Petchey et al, 2009;Moreira et al, 2016;Goździejewska et al, 2019a). Many studies have shown that zooplankton functional traits can be homogenized due to extreme environmental gradients including high trophic and primary productivity (Moody & Wilkinson, 2019), high salinity (Gutierrez et al, 2018), small or large suspended particles (Goździejewska et al, 2019a), high anthropogenic impact (Simões et al, 2020). In turn, an intermediate range of factors or spatial variation in conditions (e.g.…”
Section: Introductionmentioning
confidence: 99%